Criterion-referenced and norm-referenced agreement between the mile run/walk test and the one-and-a-half mile run/walk test and the pacer test - Hashim, Ahmad; Madon, Mohd Sani
Purpose – The purpose of this study was to test the reliability of the Mile Run/Walk Test and One-and-a-Half Mile Run or Walk Test,and the PACER Test 20-m, multistage shuttle run using criterion reference and norm reference as a working framework. Method – The sample for the study comprised 2,056 students, with male (n = 1159) and female (n = 897) randomly selected using stratifi ed random sampling, from the whole population of students aged 13, 14, and 15 years from 18 secondary schools throughout Perak, Malaysia. Two trials of the PACER Test and one each of the Mile Run/Walk Test and One-and-a-Half Mile Run/Walk Test were performed. The estimated criterion referenced reliability for the Mile Run/Walk Test and the One-and-a-Half Mile Run/Walk Test, and the PACER Test was obtained using the proportion of agreement (Pa) and ‘modified kappa (Kq) on FITNESSGRAM® Standards (Baumgartner, Jackson, Mahar, & Rowe, 2003) and the American College of Sports Standards (ACSM, 1999). Findings – Results of the study showed that the Pacer Test had high reliability for testing the maximum volume of oxygen among male and female students aged 13, 14, and 15 years old. The statistical analysis indicated a positive and strong correlation between test scores and repeated tests for the Pacer Test on male and female students aged 13, 14 and 15 years old with r = 0.94 to 0.97; 0.95 to 0.97 respectively, and was signifi cant (p<.05).Value – It is recommended that the PACER Test be used as a component of the Physical Fitness Test battery to replace the Mile Run/Walk Test and the One-and-a-Half Mile Run or Walk Test, which are still used by the Malaysian Ministry of Education,Teacher Education Division,Curriculum Development Centre, and also State Education Departments to test students’ cardiovascular resistance.